Manajemen Pembelajaran dalam Penjaminan Mutu Pendidikan (Studi Multi Situs di SMA Negeri 1 dan SMA Negeri 3 Pamekasan) - Efendy, Hadaie (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2018)
State Senior High School (SMAN 1 Pamekasan) and Vocational High School (SMK 3 Pamekasan) which both have excellent class programs in managing learning that are used for superior class programs are essentially the same as learning management for regular programs. The difference is in the development of learning management to fulfill the needs of students who have potential intelligence and special talent. Learning management is expected to play a role in empowering students. This study aims to analyze and describe: (1) Lesson plan, (2) Lesson organizing, (3) implementation of learning, (4) learning monitoring, (5) evaluating learning in assurance of education quality, (6) the quality of education produced, (7) learning obstacles in assurance of education quality. The type of this research is qualitative descriptive with the design of multi-site study. the results of this study found (1) learning plan is carried out by team work, performance meetings and decision of priority programs, (2) organizing the learning in assurance of education quality carried out by teachers who are allied in one subject matter, material, content selection, structuring content, integrating quality academic to succeed in the international science olympiad by not abandoning students’ character values and qualified output, (3) the implementation of learning involves students' mental and physical processes, (4) learning monitoring is done comparing the results of previous monitoring with government regulations, (5) evaluation learning involves all elements with the existence of reward and punishment, (6) the quality of education produces students with academic and non-academic achievements, obtains great trust from the society where the graduates are accepted in favorite state universities, (7) the constraints namely curriculum policy which often changes, the ideal student books are still limited, new assessment systems and different interpretations by each teacher, the culture of research is still limited.